2009
DOI: 10.1021/ma9001269
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Annealing on Microstructure and Mechanical Properties of Isotactic Polypropylene with β-Phase Nucleating Agent

Abstract: The microstructure and mechanical properties of β-nucleated iPP before and after being annealed at different temperatures (90-160 °C) have been analyzed. Annealing induced different degrees of variation in fracture toughness of β-nucleated iPP samples, namely, slight enhancement at relatively low annealing temperatures (<110 °C) and great improvement at moderate temperatures (120-130 °C), whereas dramatic deterioration at relatively high temperatures (>140 °C) has been observed. The variation of fracture tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
178
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(193 citation statements)
references
References 74 publications
(160 reference statements)
13
178
2
Order By: Relevance
“…In Fig. 2d, the melting peak of PA 66 nanofiber bundles appears at 260°C, which is much higher than that of iPP melting (mainly below 175°C [30]). It implies that the PA 66 nanofiber bundle would be solid state during the process of composite preparation and erasing the thermal history at 200°C.…”
Section: Resultsmentioning
confidence: 87%
“…In Fig. 2d, the melting peak of PA 66 nanofiber bundles appears at 260°C, which is much higher than that of iPP melting (mainly below 175°C [30]). It implies that the PA 66 nanofiber bundle would be solid state during the process of composite preparation and erasing the thermal history at 200°C.…”
Section: Resultsmentioning
confidence: 87%
“…The other diffraction peaks at 2θ014.0°, 16.7°, 18.5°can be attributed to the reflection of (110), (040), and (130) planes of α-iPP, respectively. This means that although TMB-5 is an effective β-NA for iPP [19,20,23,24], it does not prevent the nucleation and growth of α-lamellae. This is very important because it possibly influences the crystallization behavior of iPP/TMB-5 sample under high pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Both β-iPP and γ-iPP are thermodynamically metastable phases with heat of fusion of 168.5 [8] and 150 J/g [5], respectively, and only can be obtained under special conditions. For β-iPP, although the shear condition and temperature gradient provoke the nucleation and growth of β-iPP, addition of an active β-phase nucleating agent (β-NA) is proved to be the most efficient way to obtain iPP articles with high content of β-iPP [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. For γ-iPP, it is already known that crystallization under high pressure (>200 MPa) is the main way to achieve high content of γ-iPP [25][26][27][28] in common iPP.…”
Section: Introductionmentioning
confidence: 99%
“…22 The decreases in r Y and E f of the P1 group in Figure 1 could be interpreted by the increasing content of b crystals in iPP formed in the blends and were consistent with previously reported results. 23 Because the amino group in the b-NA may have caused some interactions with the hydroxyl group in the PA6 molecular chains, in the A1 group, the b-NA was encapsulated in the PA6 phase, and it was difficult for the nucleating agent to transfer into the iPP matrix. So, a relatively low content of b-NA in the PP matrix did not induce a large amount of b-iPP in the blends of the A1 group.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…24 It is generally considered that the content of b-iPP is the main factor determining the toughness of iPP; however, recently, Luo et al 25 adopted different molten temperatures to prepare samples with constant b-NA contents and demonstrated that the paramount factor was the connection between the crystallites instead of the b-iPP content. Bai et al 23 suggested that critical and supercritical b-NA contents led to different supermolecular structures because of its various dissolutions among the iPP matrix, such as a bundlelike morphology with a high content of b-NA and a finely dispersed form at a low content.…”
Section: Mechanical Propertiesmentioning
confidence: 99%